Exchange biased anomalous Hall effect driven by frustration in a magnetic kagome lattice - Lachman, Ella; Murphy, Ryan A.; Maksimovic, Nikola; Kealhofer, Robert; Haley, Shannon; McDonald, Ross D.; Long, Jeffrey R.; Analytis, James G. (Nature communications, 2020)
Co 3 Sn 2 S 2 is a ferromagnetic Weyl semimetal that has been the subject of intense scientific interest due to its large anomalous Hall effect. We show that the coupling of this material’s topological properties to its magnetic texture leads to a strongly exchange biased anomalous Hall effect. We argue that this is likely caused by the coexistence of ferromagnetism and geometric frustration intrinsic to the kagome network of magnetic ions, giving rise to spin-glass behavior and an exchange bias. The Weyl semimetal Co 3 Sn 2 S 2 exhibits a combination of magnetic ordering with a large anomalous Hall effect. Lachman et al. find an intrinsic exchange bias of this anomalous Hall effect and attribute it to the coexistence of ferromagnetism and spin glass behaviour.